2018
DOI: 10.5620/eht.e2018003
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and modeling of indoor radon concentrations in residential buildings

Abstract: Radon, the primary constituent of natural radiation, is the second leading environmental cause of lung cancer after smoking. To confirm a relationship between indoor radon exposure and lung cancer, estimating cumulative levels of exposure to indoor radon for an individual or population is necessary. This study sought to develop a model for estimate indoor radon concentrations in Korea. Especially, our model and method may have wider application to other residences, not to specific site, and can be used in situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…House type characteristics and type of foundations have been examined in recent studies using survey questionnaires, as was done in this study [14][15][16]18]. In these environmental research studies, the authors used questionnaires to collect data on the type of house, building characteristics, cracks in the foundation, use of groundwater, and ventilation factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…House type characteristics and type of foundations have been examined in recent studies using survey questionnaires, as was done in this study [14][15][16]18]. In these environmental research studies, the authors used questionnaires to collect data on the type of house, building characteristics, cracks in the foundation, use of groundwater, and ventilation factors.…”
Section: Discussionmentioning
confidence: 99%
“…House ventilation characteristics have also been assessed in recent studies by characterizing the usage of ventilation systems and infiltration factors [14,15]. In this study, ventilation was assessed by comparing indoor radon levels in homes with a crawl space to homes without a crawl space.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we focused only on factors shown to affect indoor radon concentrations in previous studies, such as soil, building materials, outdoor air, and ventilation. In Park et al [5], the following system of differential equations for estimating indoor radon concentrations was presented based on a mass balance equation by modifying a model suggested by Font et al [12] and Arvela et al [13] as follows:dCidt={kd,s(CsCi)+kaΔPsiCs}SgV+kd,bm(CbmCi)SbmVλv(CiCo)λCi,dCsdt=EsSgV{kd,s(CsCi)+kaΔPsiCs}SgVλCs,…”
Section: Methodsmentioning
confidence: 99%
“…These models and applications were previously reviewed by Park et al [4] who found them to be applicable only to specific regions or situations or to require actual measurement data. For Korea, Park et al [5] developed a model for estimating indoor radon concentrations using data from surveys between January and April 2016. While this model offered wider application for a number of residences, not to a specific site, and could be used in situations where actual measurements for input variables were lacking, the model was only of use for estimating indoor radon concentrations for detached houses.…”
Section: Introductionmentioning
confidence: 99%